PIAAC’s role in global food security: Evidence from machine learning-based feature selection across three major food security indicators - Sneha Roy; Jeffrey Zacharakis (Adult Education Research Conference, 2023)
The PIAAC country dataset for 36 countries is explored to understand its role in global food security, adding to its significance in sustainable development goal four, zero hunger.
Keywords: PIAAC; food security; adult; skills; sustainable development